LITTER PRODUCTION OF Rhizophora Mangle AT BACALAR CHICO, SOUTHERN QUINTANA ROO, MEXICO - de Jesús Navarrete, Alberto; Oliva Rivera, José Juan (Ecosistemas y Recursos Agropecuarios, 2014)
In order to know the litter fall of the red mangove, Rhizophora mangle, samples were collected from July 1996 to July 1997 in the channel of Bacalar Chico in southern of Quintana Roo state. Litter was collected bimonthly in duplicate baskets at five sites. Four mangrove species were present in the study area, but R. mangle dominated widely. Leaf production comprised 99.8% of total litter fall biomass, being the highest in July and September 1996 (0.27 g·dry wt·m-2·day-1 and 0.28 g·dry wt·m-2·day-1 respectively). Although, the flowers and the fruits represented less of 1% of total litter production, it was clear that the reproductive season was coincident with the highest values of temperature and precipitation, both occurring in September. Mangrove in Quintana Roo produced a total litter fall of 2.61 t dry wt ha-1year-1. Mangroves of Quintana Roo must be protected and used with conservation criteria.
Keywords: coastal zone; litter fall; Rhizophora mangle; Quintana Roo; Mexico